Extracellular vesicles-derived OncomiRs mediate communication between cancer cells and cancer-associated hepatic stellate cells in hepatocellular carcinoma microenvironment. (29th May 2019) - Li, Jiang; Yan, Yan; Ang, Lin; Li, Xiaoya; Liu, Chunying; Sun, Bin; Lin, Xuejing; Peng, Zhangxiao; Zhang, Xiaofeng; Zhang, Qin; Wu, Hongping; Zhao, Min; et al.
Abstract: Tumor microenvironment (TME) is a critical determinant for hepatocellular carcinoma (HCC). Hepatic stellate cells (HSCs) are main interstitial cells in TME and play a vital role in early intrahepatic invasion and metastasis of HCC. The potential mechanism on the interactions between HSCs and HCC cells remains unclear. In this study, the effects of extracellular vesicles (EVs)-derived OncomiRs that mediate communication between HCC cells and cancer-associated hepatic stellate cells (caHSCs) and remold TME were investigated. The results found that the HCC cells-released EVs contained more various OncomiRs, which could activate HSCs (LX2 cells) and transform them to caHSCs, the caHSCs in turn exerted promotion effects on HCC cells through HSCs-released EVs. To further simulate the effects of OncomiRs in EVs on construction of pro-metastatic TME, a group of OncomiRs, miR-21, miR-221 and miR-151 was transfected into HCC cells and LX2 cells. These microRNAs in the EVs from OncomiRs-enhanced cells were demonstrated to have oncogenic effects on HCC cells by upregulating the activities of protein kinase B (AKT)/extracellular signal-regulated kinase (ERK) signal pathways. Equivalent results were also found in HCC xenografted tumor models. The findings suggested that the OncomiR secretion and transference by cancer cells-released EVs can mediate the communication between HCC cells and HSCs. HCC cells and caHSCs, as well as their secreted EVs, jointly construct a pro-metastatic TME suitable for invasion and metastasis of cancer cells, all these TME components form a positive feedback loop to promote HCC progression and metastasis. Abstract : OncomiRs, highly expressed in HCC cells, are very meaningful to remold TME. HSCs are important component in TME. The cancer cells-secreted OncomiRs through EVs mediate the formation of metastasis-promoting pro-microenvironment by the bidirectional interaction between cancer cells and HSCs.